Non-descent vaginal hysterectomy: should all hysterectomies for benign conditions be performed vaginally? - Nusee, Zalina (Obstetrical and Gynaecological Society of Malaysia, 2019)
The vaginal approach is the natural route of excellence, also known as “natural orifice hysterectomy” or “no scar hysterectomy”. It seems to be the current trend in minimally invasive context for urogynecological procedure, which follows all criteria of minimally invasive surgery. Vaginal hysterectomy (VH) is a longpracticed procedure since the fourteenth century (Berengario de Carpi, 1470–1550). Non-descent vaginal hysterectomy (NDVH) was introduced later in 1934, pioneered by Haeney. In the United States, the trend is now more towards NDVH, especially with the presence of new tools (vessels sealing device), new techniques and changes in contraindications of the procedure.